Inuit materials, Alfred Irving Hallowell Papers - Hallowell, A. Irving (Alfred Irving), 1892-1974; Freuchen, Peter, 1886-1957 (1930)
The Inuit materials in the Hallowell Papers include notes on ethnographic materials, analyses of myths, shamanism, property, racial identification, anthropometry, and somaltology. There are newspaper clippings, one entitled "Artic Adventure" by Peter Freuchen and reading notes from secondary sources.